The devil's milk : a social history of rubber - Tully, John A. (John Andrew) (Monthly Review Press, 2011)
Capital, as Marx once wrote, comes into the world "dripping from head to foot, from every pore, with blood and dirt." He might well have been describing the long, grim history of rubber. From the early stages of primitive accumulation to the heights of the industrial revolution and beyond, rubber is one of a handful of commodities that has played a crucial role in shaping the modern world, and yet laboring people around the globe have every reason to regard it as "the devil's milk." All the advancements made possible by rubber industrial machinery, telegraph technology, medical equipment, countless consumer goods have occurred against a backdrop of seemingly endless exploitation, conquest, slavery, and war. But, as John Tully reminds us, the vast terrain of rubber production has always been a site of struggle, and the oppressed who toil closest to "the devil's milk" in all its forms have never accepted their immiscration without a fight. This book, the product of exhaustive scholarship carried out in many countries and on several continents, is destined to become a classic. With the skill of a master historian and the elegance of a novelist, Tully presents what amounts to a history of the modern world told through the multiple lives of rubber. --Book Jacket